2019
DOI: 10.1038/s42003-019-0281-1
|View full text |Cite|
|
Sign up to set email alerts
|

SnRK2 protein kinases represent an ancient system in plants for adaptation to a terrestrial environment

Abstract: The SNF1-related protein kinase 2 (SnRK2) family includes key regulators of osmostress and abscisic acid (ABA) responses in angiosperms and can be classified into three subclasses. Subclass III SnRK2s act in the ABA response while ABA-nonresponsive subclass I SnRK2s are regulated through osmostress. Here we report that an ancient subclass III SnRK2-based signalling module including ABA and an upstream Raf-like kinase (ARK) exclusively protects the moss Physcomitrella patens from drought. Subclass III SnRK2s fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 53 publications
3
100
0
3
Order By: Relevance
“…SnRK2s may then be activated by autophosphorylation and/or transphosphorylation by several other kinases, such as the Raf‐like MAKKKs, RAF10, and ARK (for ABA and abiotic stress‐responsive Raf‐like kinases) (Figure 2). These kinases appear to be critical for the activation of SnRK2s and subsequent responses to ABA and abiotic stresses in Arabidopsis and Physcomitrella patens (Huang et al 2014; Lee et al 2015; Saruhashi et al 2015; Stevenson et al 2016; Hwang et al 2018; Nguyen et al 2019; Shinozawa et al 2019). BRASSINOSTEROID INSENSITIVE 2 (BIN2), the Glycogen synthase kinase 3s (GSK3s)/Shaggy‐like kinases (ASKs) repress brassinosteroid (BR) signaling, whereas they enhance ABA signaling through specifical phosphorylation of SnRK2.2/3 at Thr180 on SnRK2.3, but not SnRK2.6 (Cai et al 2014).…”
Section: Core Aba Signalingmentioning
confidence: 99%
“…SnRK2s may then be activated by autophosphorylation and/or transphosphorylation by several other kinases, such as the Raf‐like MAKKKs, RAF10, and ARK (for ABA and abiotic stress‐responsive Raf‐like kinases) (Figure 2). These kinases appear to be critical for the activation of SnRK2s and subsequent responses to ABA and abiotic stresses in Arabidopsis and Physcomitrella patens (Huang et al 2014; Lee et al 2015; Saruhashi et al 2015; Stevenson et al 2016; Hwang et al 2018; Nguyen et al 2019; Shinozawa et al 2019). BRASSINOSTEROID INSENSITIVE 2 (BIN2), the Glycogen synthase kinase 3s (GSK3s)/Shaggy‐like kinases (ASKs) repress brassinosteroid (BR) signaling, whereas they enhance ABA signaling through specifical phosphorylation of SnRK2.2/3 at Thr180 on SnRK2.3, but not SnRK2.6 (Cai et al 2014).…”
Section: Core Aba Signalingmentioning
confidence: 99%
“…Still, we cannot exclude that AtSCS-A also inhibits the ABA-nonresponsive SnRK2s, because AtSCS-A in contrast to AtSCS-B interacts not only with the ABA-activated SnRK2s but also with the kinases of group 1, which are not activated by ABA. However, the evolution studies performed by Holappa et al (2017) have shown that SCS proteins appeared in the earliest land plants at about the same time as the ABA receptors Regulatory Component of ABA Receptor/Pyrabactin Resistance1/PYR1-like, PP2Cs, and ABA-activated SnRK2s (from group 3) that constitute the prototype of the SnRK2 family Komatsu et al, 2013;Shinozawa et al, 2019). The ABA-nonresponsive SnRK2s evolved later, in vascular plants.…”
Section: Discussionmentioning
confidence: 99%
“…Still we cannot exclude that AtSCS-A also inhibits the ABA-non-responsive SnRK2s, since AtSCS-A in contrast to AtSCS-B interacts not only with the ABA-activated SnRK2s but also with kinases of the group 1, which are not activated by ABA. However, the evolution studies performed by Holappa et al (2017) have shown that SCS proteins appeared in earliest land plants at about the same time as ABA receptors - RCAR/PYR/PYL (RCAR, Regulatory Component of ABA Receptor/PYR1, Pyrabactin Resistance 1/PYL, PYR1-like), PP2Cs (Umezawa et al, 2010; Komatsu et al, 2013; Shinozawa et al, 2019), and ABA-activated SnRK2s (from group 3) that constitute the prototype of the SnRK2 family. The ABA-non-responsive SnRK2s evolved later, in vascular plants.…”
Section: Discussionmentioning
confidence: 99%